The role of speech therapy in the therapy of children with central hearing disorders - Agnieszka Kasperczuk-Bajda; Monika Wybraniak; Antoni Niedzielski (Kazimierz Wielki University, 2017)
Central disorders of hearing processing are one of the main causes of school difficulties among children. CAPD is described as incapability of using auditory acoustic sounds with its correct perception within ambit structures. The disorder is often accompanied by such difficulties as dyslexia, specific learning problems or subnormal speech development. Early diagnose of the  disorder and commencing a therapy allows a child a better adjustment to expectations which he or she is exposed to by its environment. The aim of this work is indicating the role and abilities of a speech therapist while treating CAPD children. Aural training is adequate for children with central auditory disorders and in order to be effective it should be long lasting, intensive and adjusted to a child's individual abilities. Therapy should include both passive listening of sounds and exercises in which the child can actively participate. The aim of speech therapy is to develop auditory skills, speaking, communication and stimulating cognitive potential of a child. Among the auditory exercises conducted by the speech therapist are understanding distorted speech exercises, understanding distorted speech in the presence of a jamming signal, separation and integration of information exercises. localization and lateralization exercises, recognizing sound patterns exercises, recognizing sound sequences exercises, differentiating nonverbal stimuli and phonemes exercises and prosodic training. Therapeutic auditory training that is carried out systematically develops aural and linguistic competences.